Visa Relaxation Policies and Potential Implications on Public Health in Africa - Komakech, Allan; Baki, Karl Angendu; Izudi, Jonathan (Journal of Travel Medicine, 2024)
In November 2023, Rwanda adopted visa-free travel for all Africans. Kenya also began visa-free entry in January 2024. Between 2016 and 2023, the landscape of international travel in Africa remarkably changed due to policy reforms. Several African Union member states have relaxed their visa laws and requirements to open new trade as part of the African Continental Free Trade Area,1 tourism and travel avenues
Keywords: Visa relaxation; Policies; Public health; Africa